Humanizing practices in online learning communities during pandemics in the USA. Issue 3 (4th November 2020) - Abdi, Nimo M.; Gil, Elizabeth; Marshall, Stefanie LuVenia; Khalifa, Muhammad
Abstract : Purpose: In this reflective essay, the authors, four educators of color, explore the relevance of humanizing practices of community in teaching and learning, school leadership and the potential challenges for equity work in education, during the COVID-19 pandemic. Design/methodology/approach: This reflective essay draws on lessons learned from the pedagogical practices of women of color, literature on teachers of color, as well as our experiences as educators of teachers and school leaders, as the authors think about new possibilities and challenges for anti-racist practice and living during the pandemic. Findings: This essay describes community-oriented practice of women of color educators to be important in orienting teaching and learning toward more humanizing practice. The reflections highlight both possibilities and challenges that can be helpful reimagining the practice in teacher and leadership education, as the authors prepare educators for an uncertain future. Originality/value: This essay offers valuable lessons from women of color educator practice that can offer humanizing approaches to teaching and learning as well as school leadership education.